Suicide ideation and behavior in Mexico: Encodat 2016 - Guilherme Borges; Ricardo Orozco; Jorge Villatoro; Maria Elena Medina-Mora; Clara Fleiz; Jessica Díaz-Salazar (Instituto Nacional de Salud Pública, 2018)
Objective. To provide updated information regarding the 12-month prevalence and associated sociodemographic factors for suicide ideation and behavior (plan and attempts) to substantiate preventive programs in Mexico. Materials and methods. Cross-sectional nationally representative survey, conducted during 2016 (n=56 877) among those 12-65 years old living in rural, urban and metropolitan dwellings. Results. The prevalence of suicide ideation in the last 12-months was 2.3%, 0.8% of the sample reported a plan and 0.7% reported a suicide attempt. All three outcomes were about two times more common among females and suicide plan and attempt were less common among the elderly (50-65 years old). Suicide attempts were more common in urban than in rural areas. The state of Tabasco showed an increased prevalence of ideation, plan and attempts when compared to national average rates. Conclusions. Public health measures to diminish and treat suicidal behavior are urgently needed all over the country.